Dampak Perilaku Pemimpin Paradox Terhadap Kinerja Bawahan Melalui Keterbukaan Pengalaman dan Orientasi Tujuan Pembelajaran - Dian Palupi; Suhermin; Mohammad Faisal; Candraningrat (Ekonomi dan Bisnis, 2025)
Purpose: This study aims to analyze how openness to experience and learning goal orientation influence paradoxical leader behavior and the mediating effect of paradoxical leader behavior and the moderating effect of psychological capital on follower performance. Design/methodology/approach: This research is a quantitative research, using PLS-SEM data analysis. The sampling method uses purposive sampling. The respondents were 102 lecturers and administrative staff at universities who had subordinates. Questionnaires were distributed to collect data Findings: Significant results were shown by openness to experience on paradox leader behavior, as well as learning goal orientation on paradoxical leader behavior and learning goal orientation on follower performance. The results showed that paradoxical leader behavior neither did mediate openness to experience nor learning goal orientation on follower performance, Meanwhile, insignificant results were also shown by openness to experience on follower performance, and paradoxical leader behavior on follower performance. In addition, there was no moderating effect of psychological capital on paradoxical leader behavior on follower performance. Research limitations/implications: This study has limitations, as the population in this study only came from private universities in Indonesia. Future research could be expanded to include public universities or other demographic groups/sectors and adding other variables to deepen understanding of the relationship between these variables. Practical implications: The results of the study indicate that leaders and foundations at private universities need to develop a culture and create a work environment through rules and policies that emphasize learning goal orientation and openness to experience to encourage adaptive paradoxical leadership behavior. Employees who understand paradoxical leader behavior can see conflicting and competing demands as phenomena in the organization and can integrate various demands so that the contradictions between them can be productive. Originality/value: This research contributes to the implementation of Paradox Theory and Personality Traits in influencing the performance of subordinates among lecturers at private universities in Indonesia. This represents a research gap and is interesting because there is not much research on this topic. Paper Type: This article is a research paper examining the influence of openness to experience and learning goal orientation on paradoxical leader behavior, the mediating effect of paradoxical leader behavior, and the moderating effect of psychological capital on follower performance. Keywords: Paradox leader behavior; openness to experience; learning goal orientation; follower performance, psychological capital.